Project synthesis using compromise-compensating model in decision support system in construction industry/Projektų sintezė naudojant kompromiso kompensacinius modelius statyboje - Šarka, Vaidotas; Ustinovičius, Leonas; Zavadskas, Edmundas K. (Journal of Civil Engineering and Management, 1999)
The primary goal for development of project decision support system is to optimise design of rational lifetime processes of a building. An efficient realisation of construction projects requires analysing their constituent parts in close interdependent relationship. This can be reached by applying three methods of project synthesis in computer software “Universal decision support system in construction” with database of various construction project variants. Thus for carrying out a multicriteria synthesis of various projects and selecting the highest quality alternatives, it is necessary: – to develop all feasible alternative variations; – to develop a system of attributes able to produce a detailed description of the alternatives; – to calculate values and significances of the attributes; – to develop relation system between alternative variations. On a UniDSS methodological basis, a technological model of the selections of the most efficient construction elements (main walls, foundations, roof, windows, internal walls) of the real project, Polish house near Naugarduko-Kaunas street crossing, using synthesis, with compromise-compensating model, was developed.Article in Lithuanian.First Published Online: 26 Jul 2012